1979
DOI: 10.1203/00006450-197901000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Tracheal Explant Bioassay for the Detection of the Ciliary Dyskinesia Factor in Cystic Fibrosis Serum

Abstract: SummaryA tracheal ring explant system, when used with 25% cystic fibrosis (CF) serum, displayed obvious ciliostasis. Hamster, rabbit, and guinea pig explants all had measurable decreases in ciliary activity after 24 hr of incubation in the serum. The differential response to CF serum (relative to normal serum) was greatly increased by using explants which were maintained 24-72 hr in i*dnimal essential medium (MEM) with 10% horse serum and which were selected on the basis of optimal ciliary activity and vigor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…In agreement with the recent work of others (Blitzer and Shapira, 1982;Gabridge et al, 1979) we have demonstrated that CF serum stimulates mucus droplet formation from the cells lining tracheal explants, as observed by scanning electron microscopy. The advent of methods for culturing HTE cells (Goldman and Baseman, 1980a,b) prompted us to attempt similar experiments with the isolated cells of the tracheal lining in the expectation that sensitivity of CF factor would be a property of the individual cells and not just of the intact explant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with the recent work of others (Blitzer and Shapira, 1982;Gabridge et al, 1979) we have demonstrated that CF serum stimulates mucus droplet formation from the cells lining tracheal explants, as observed by scanning electron microscopy. The advent of methods for culturing HTE cells (Goldman and Baseman, 1980a,b) prompted us to attempt similar experiments with the isolated cells of the tracheal lining in the expectation that sensitivity of CF factor would be a property of the individual cells and not just of the intact explant.…”
Section: Discussionsupporting
confidence: 93%
“…Various sera were added to a final concentration of 25%, and, after incubation at 37 "C for increasing times, the rings were removed and processed for SEM. This protocol is essentially that which Gabridge et al (1979) used to observe the discharge of mucus droplets by tracheal goblet cells. Resulting micrographs show that CF serum (Fig.…”
Section: Effects Of Serum On Tracheal Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in ciliary activity observed in this study are particularly relevant to bioassay studies used for the detection of the disease cystic fibrosis (CF). These assays rely on a differential effect of normal and CF (homo-or heterozygote) serum on ciliary activity (Spock et al, 1967;Conover et al, 1973;Bowman et al, 1977;Gabridge et al, 1979), usually ascribed to the presence of a "CF factor." The inhibition or changes in ciliary activity (ciliary dyskinesia) observed by these authors could result from a reaction between serum IgM and the ciliated tissue used.…”
Section: Discussionmentioning
confidence: 99%
“…In the difficult search for a molecular component which might be the CF causative agent, perhaps the most consistent finding has been that serum from CF patients contains a factor which may be responsible for the etiology of the disease (Gabridge et al, 1979;Nagy et al, 1979;Kurlandsky et al, 1980;Impero et al, 1981;McNeely et al, 1982;Carson and Bowman, 1982; Mc-Pherson et al, 1983). Such factors have been isolated by 0 1984 ALAN R. LISS, INC several groups on the basis of their ability to inhibit ciliary activity in tracheal explants or oyster gills (Conover and Conod, 1978;McNeely et al, 1982; Carson and Bowman, 1982), and have proved to be low molecular weight (5-10 kdaltons), cationic glycoproteins reportedly associated with IgG (Danes, 1973;Blitzer and Shapira, 1982).…”
mentioning
confidence: 99%